2008
DOI: 10.1186/1297-9686-40-5-511
|View full text |Cite
|
Sign up to set email alerts
|

Inbreeding depression on beef cattle traits: Estimates, linearity of effects and heterogeneity among sire-families

Abstract: -Records from up to 19 054 registered cows and 10 297 calves in 155 herds of the Alentejana cattle breed were used to study the effects of individual (F i ) and maternal (F m ) inbreeding on reproductive, growth and carcass traits, as well as assessing the importance of non-linear associations between inbreeding and performance, and evaluating the differences among sire-families in the effect of F i and F m on calf weight at 7 months of age (W7M). Overall, regression coefficients of performance traits on inbre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
33
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 34 publications
(24 reference statements)
4
33
1
Order By: Relevance
“…According to Carolino and Gama (2008), the frequently assumed linear association between inbreeding and performance is compatible with the dominance hypothesis, as it would correspond to the loss of heterozygosity and an increase in the frequency of deleterious recessive homozygotes as inbreeding accumulates. However, if epistatic effects are also involved in inbreeding depression, a non-linear decline in mean performance would result from accumulated inbreeding (Charlesworth & Charlesworth 1999).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…According to Carolino and Gama (2008), the frequently assumed linear association between inbreeding and performance is compatible with the dominance hypothesis, as it would correspond to the loss of heterozygosity and an increase in the frequency of deleterious recessive homozygotes as inbreeding accumulates. However, if epistatic effects are also involved in inbreeding depression, a non-linear decline in mean performance would result from accumulated inbreeding (Charlesworth & Charlesworth 1999).…”
Section: Resultsmentioning
confidence: 93%
“…In a review, Burrow (1993) reported decreases of 0.44 kg/1% for weaning weight and 0.69 kg/1% for W365 of calves. According to Carolino and Gama (2008), the high results presented by Burrow (1993) are mostly based on highly inbred lines of cattle, while their data originated from commercial herds subject to mild artificial selection and with moderate rates of inbreeding, thus with lower expected effects of inbreeding depression. At lower levels of inbreeding the linear model provides a reasonable approximation of the phenomenon.…”
Section: Resultsmentioning
confidence: 99%
“…Santana et al (2010), studying Nellore animals, also found an unfavorable effect of F i on WW. Burrow (1998) and Carolino and Gama (2008) also reported an inbreeding depression of −0.32 to −1.49 kg/1% increase in F i on BW at 12 and 18 mo of age of beef cattle. The estimates of inbreeding depression indicate that the lack of control of inbreeding in the populations will result in economic losses for production systems.…”
Section: Inbreeding Depressionmentioning
confidence: 99%
“…The application of quantitative breeding methodology and reproductive biotechnology (artificial insemination) has resulted in more intense selection pressure on a number of traits of economic importance that might have contributed to an increase in production efficiency, but in some cases at the expense of genetic diversity. The use of a small number of elite genotypes poses the danger of increasing undesirable recessive genes within a population that may result in inbreeding depression in the long run (Carolino & Gama, 2008;Oltenacu & Broom, 2010). The loss of genetic diversity due to increased inbreeding within cattle breeds has been reported to have negative effects on some production and fitness traits in dairy (Oltenacu & Broom, 2010) and beef cattle breeds (Carolino & Gama 2008;Santana et al, 2010).…”
mentioning
confidence: 99%
“…The use of a small number of elite genotypes poses the danger of increasing undesirable recessive genes within a population that may result in inbreeding depression in the long run (Carolino & Gama, 2008;Oltenacu & Broom, 2010). The loss of genetic diversity due to increased inbreeding within cattle breeds has been reported to have negative effects on some production and fitness traits in dairy (Oltenacu & Broom, 2010) and beef cattle breeds (Carolino & Gama 2008;Santana et al, 2010). Maintenance of within-breed genetic diversity is therefore essential in making selection decision for genetic improvement.…”
mentioning
confidence: 99%